The Positive Effects of Implementing Motion Analysis and Sport Biomechanics Technologies in Young Tennis Athletes’ Training: A Community Service Approach - Muchamad Arif Al Ardha; Panji Bana; Dani Primanata; Mochamad Purnomo; Oce Wiriawan; Sauqi Sawa Bikalawan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to evaluate tennis training in young athletes with the suitability of resources and techniques used by athletes. A qualitative method with a case study design was used in this research. The study involved 15 tennis athletes with an age range of 10-17 years, who followed a training program for beginners. The data collection process involves athletes and parents by using semi-structured interviews. The data were subjected to thematic analysis, including the process of identifying, analyzing, and interpreting the data. According to this study, implementing motion analysis and sport biomechanics into young tennis training enhances long-term skills, confidence, and performance while lowering injury rates. Athletes are inspired and dedicated to their training because the visualized feedback from captivating technology. Biomechanics and motion analysis may revolutionize young sports training by improving performance and establishing new benchmarks. These tech-enabled initiatives support young athletes' success while protecting their health and welfare.